PERANCANGAN BISNIS MIND PRODUCTION DI SURABAYA - Michael Prayogo Santosa; Marina Wardaya (Jurnal Vicidi, 2016)
Mind Production is a conceptual video producer company for Indonesian Hip- Hop dancer which is produce the video with the best concept and quality, also adding the value of Indonesia onto the concept to show the quality of Indonesian talents. The purpose of this research is to build a conceptual video producer business. There are 2 methods that are going to be use in this research, quantitative (questionnaire) and qualitative (interview). Hopefully from this research the researcher could build the right Business.